Eco-Friendly Shrimp Farming: Balancing Economic Growth and Environmental Sustainability in Agriculture - Ahmed, Rashed (International Journal of Science Education and Science, 2025)
Eco-friendly shrimp farming is emerging as a transformative approach in aquaculture, addressing the economic and environmental challenges associated with conventional practices. This article provides a comprehensive exploration of the topic, highlighting its methodologies, impacts, challenges, and future prospects.Eco-friendly shrimp farming integrates sustainable practices such as integrated multi-trophic aquaculture (IMTA), biofloc technology, and renewable energy to minimize ecological degradation while enhancing economic profitability. The approach significantly reduces mangrove deforestation, improves water quality, and lowers greenhouse gas emissions, contributing to global conservation goals. Economically, it fosters cost efficiency, premium market access through certifications, and sustainable livelihoods, particularly benefiting marginalized communities. However, challenges such as high initial costs, the need for technical knowledge, and regulatory barriers pose significant hurdles to adoption. Addressing these requires strategic interventions, including financial support, capacity-building programs, and robust policy frameworks. The article also emphasizes the importance of consumer awareness and collaboration among stakeholders, from farmers to policymakers, in advancing eco-friendly shrimp farming. Future directions include research on scalable technologies, education campaigns to boost demand for sustainably sourced shrimp, and international partnerships to enhance knowledge exchange. By balancing economic gains with environmental conservation, eco-friendly shrimp farming presents a viable path toward sustainable aquaculture, ensuring long-term benefits for both industry and ecosystems. This synthesis underscores the critical need for a concerted effort to mainstream sustainable practices in shrimp farming.